INTEGRASI PEMBIASAAN MEMBACA SURAT PENDEK UNTUK PENGUATAN NILAI-NILAI ISLAM PADA PEMEBELAJARAN PAI - Atika Rizqia Ramadhani; Ahmad Saiful Rizal; Achmad Abdul Azis (IAIN Bone, 2025)
Abstract This study aims to examine the implementation of short Surah recitation habituation as an effort to strengthen Islamic values in Islamic Religious Education (PAI) learning at SMKN 1 Blora. The study arises from the condition of vocational schools that tend to prioritize vocational skills while giving less attention to the development of religious values and character. This research employed a descriptive qualitative approach with field research methods. Data were collected through participatory observation, in-depth interviews, and documentation, involving one PAI teacher and three purposively selected twelfth-grade students. The data were analyzed using a reflexive thematic analysis technique to identify patterns and themes. The findings reveal that the teacher actively acted as both facilitator and role model by leading students to recite short Surahs for 5–10 minutes before each lesson. The habituation was carried out consistently and inclusively, initially facing challenges due to students’ limited ability in Qur’an recitation. However, through continuous guidance, motivation, and the provision of printed and digital texts, students gradually became more active participants. The practice created a religious and conducive classroom atmosphere, strengthened discipline, nurtured social attitudes, and improved Qur’an reading skills. A key factor supporting the success of this program was the active involvement of students and the teacher’s innovation in overcoming obstacles, particularly by providing accessible learning resources in both printed and digital formats to ensure inclusivity. This research concludes that the habituation of short Surah recitation serves as a simple yet effective strategy to instill Islamic values in vocational schools, with success determined by teacher exemplarity, student participation, and institutional support.